Early Cretaceous subsidence of the Naturaliste Plateau defined by a new record of volcaniclastic-rich sequence at IODP Site U1513 - Lee, Eun Young; Wolfgring, Erik; Tejada, Maria Luisa G.; Harry, Dennis L.; Wainman, Carmine C.; Chun, Seung Soo; Schnetger, Bernhard; Brumsack, Hans-Jürgen; Maritati, Alessandro; Martinez, Mathieu; Richter, Carl; Li, Yong-Xiang; et al. (Gondwana Research, 2020)
The Naturaliste Plateau is a submarine continental ribbon rifted from the southwest Australian margin during the Early Cretaceous breakup of East Gondwana. It occupied a key position near the juncture of Greater India and the boundary between Australia and Antarctica. However, details of the Early Cretaceous evolution of the plateau are not well known because of limited data. Drilling at Site U1513 during IODP Expedition 369 recovered the first complete Lower Cretaceous succession on the eastern Naturaliste Plateau. The succession includes syn-rift volcanic rocks, Hauterivian to early Aptian volcaniclastic-rich sedimentary rocks, and Albian claystone strata. The 235-m thick volcaniclastic-rich sequence represents the missing post-breakup record in the southwest Australian rifted margin. It spans the transition from syn- to post-rift phase during the final stages of breakup between Greater India and Australia-Antarctica. We report the lithological, petrophysical, geochemical, paleontological, and paleomagnetic characteristics of the sequence, and then synthesize the results to define the Early Cretaceous depositional environment and subsidence history of the Naturaliste Plateau. From the early Hauterivian, weathered volcanic products were eroded and re-deposited locally as a volcaniclastic-rich sequence, with a major contribution from the southern Naturaliste Plateau. The depositional environment evolved from a shelf to upper bathyal condition during the Hauterivian through early Barremian with a decreasing sedimentation rate. This period is defined as a late syn-rift subsidence phase by NW-SE trending extension. After the final breakup with Greater India, the plateau remained at upper bathyal depths with little deposition until the early Aptian. Mid–lower bathyal depths inferred from the Albian claystone strata suggest that the post-rift thermal subsidence commenced during the late Aptian. This two-phase post-rift subsidence reflects the proximity or high temperature of mantle plume, possibly the Kerguelen ...